Book review: Sujata Patel, D. Parthasarathy & George Jose (Eds.), Mumbai/Bombay: Majoritarian Neoliberalism, Informality, Resistance, and Wellbeing. (May 2023) - Wagle, Paroma
Sujata Patel, D. Parthasarathy & George Jose (Eds.), Mumbai/Bombay: Majoritarian Neoliberalism, Informality, Resistance, and Wellbeing . Routledge, 2022, 280 pp., ₹995, ISBN: 9781032276724.